GLOBULAR AND CORDIFORM COFFEE SOMATIC EMBRYOS INDUCED BY BAP E SUCROSE - PEREIRA, Alba Regina; PASQUAL, Moacir; CHAGAS, Edvan Alves; FRÁGUAS, Chrystiane Borges; DUTRA, Leonardo Ferreira (Scientia Agraria, 2003)
The conventional breeding programs for coffee plants require a long period for obtaining new cultivars. Techniques of tissue culture are used to minimize such problem. The effect of BAP and sucrose in somatic embryogenesis of coffee plants was evaluated. Calli of Coffea arabica L. Acaiá Cerrado were inoculated in test tubes containing 15 ml of a R regeneration semi-solid culture medium. The treatments consisted of different BAP concentrations (0, 2, 4, 6 and 8 mg.L-1) and sucrose (0, 15, 30 and 60 g.L-1), and the culture medium was supplemented with 7 g.L-1 agar. The pH was adjusted to 5.8 before being sterilized at 121 ºC and 1.5 atm for 20 minutes. The calli were inoculated in test tubes in laminar flow chamber and the cultures were kept in a growth room at 27 ± 1 ºC, 16-hour photoperiod and 32 mM.m-2.s-1 light intensity. The highest number of globular and cordiform embryos were obtained by using 8 mg.L-1 of BAP combined to 60 mg.L-1 sucrose which provided a total of 247 and 182 embryos per explant, respectively.